Social change among fulbe nomadic primary school children in Nigeria - Bello Buba, 1972-; Zainudin Hassan, supervisor; Fakulti Pendidikan (2014)
Thesis (Sarjana Pendidikan (Pendidikan dan Pembangunan)) - Universiti Teknologi Malaysia, 2014